Metals in Fishes from Yongshu Island, Southern South China Sea: Human Health Risk Assessment. (19th October 2017) - Wu, Zhai; Xu, Ye; Cai, Minggang; Cheng, Sha-Yen; Chen, Huorong; Huang, Dongren; Chen, Kai; Lin, Yan; Li, Tianyao; Liu, Mengyang; Deng, Hengxiang; Ni, Minjie; et al.
Abstract : In order to assess the bioaccumulation of metals associated with gender, tissues, and their potential ecological risk, four species of fish were collected from the Yongshu Island in the Southern South China Sea. Metals and stable Pb isotopes in their tissues (muscle, gill, liver, intestine, and ovary) were determined. The concentrations of metals (mg/kg, dry weight) in these species were ND–21.60 (Cd), 1.21–4.87 (Cr), 0.42–22.4 (Cu), 1.01–51.8 (Mn), 0.30–3.28 (Ni), 6.04–1.29 × 10 3 (Zn), 14.89–1.40 × 10 3 (Fe), and 0.22–3.36 (Pb). In general, the liver and intestine absorbed more metals than the other tissues. Metals accumulation can be influenced by gender and feeding behavior and in fact, female fish and dietary exposure are more prone to accumulate metals. In addition, Pb isotopic ratios indicated that all species had significant biological fractionation, which may not make them good tracers for source identification. The metal concentrations of most samples were lower than the national standard values of the FAO (USA), which suggested that human consumption of these species may not cause health risks. However, since the surrounding areas are developing rapidly, the potential environmental risk of metals will intensify and should receive more attention.